The effects of using an active workstation on executive function in Chinese college students. - Zhanjia Zhang; Bing Zhang; Chunmei Cao; Weiyun Chen (PLoS ONE)
This study aimed to examine the effects of active workstation use on the executive function by measuring the three components of executive function (Inhibition, Updating, and Shifting) during sitting, standing, and walking at an active workstation with different speeds. Twenty-four college students completed a cognitive test battery while sitting, standing, walking on an active workstation with a self-selected speed (mean = 2.3 km/h) and a faster speed (mean = 3.5 km/h). The three components of executive function (Inhibition, Updating, and Shifting) were assessed by Stroop task, N-back task, More-odd shifting task, respectively. Performance of each task was determined by the response time and accuracy. Repeated measures ANOVAs were conducted with workstation condition and trial type as within-subjects factors. There were no significant main effects for workstation condition and no interaction between workstation condition × trial type in Stroop task and More-odd shifting task. There was a significant main effect for workstation condition (F (3, 69) = 4.029, p = 0.011) and interaction effect between workstation condition × trial type (F (6, 138) = 9.371, p < 0.001) in N-back task. Decomposition of the interaction showed that accuracy of 2-back task in self-paced walking was significantly lower than that in sitting condition (p = 0.017) and in standing condition (p < .001). But there was no difference in accuracy of 2-back task between self-paced walking condition and faster walking condition (p = 0.517). Our results suggest that using an active workstation may have a selective impact on three components of executive function, in which the Updating may be impaired to a certain extent while the Inhibition and Shifting remain unaffected.